Administrative and Legal Principles for Determining the Legal Regime of Using Forestry Resources as an Important Component of Nature-Oriented Complex of Ukraine (Bulletin of Kharkiv National University of Internal Affairs, 2019)
The author has studied the concept and content of the legal regime in the general sense and through the prism of the sphere of research of the forestry fund of Ukraine.The elements and features of the legal regime of forestry resources of general and special purpose have been characterized. The author has offered own definition of the concept of “legal regime of the forestry fund”.It has been emphasized that the effective protection of the forestry fund as an important component of the country’s nature-oriented complex depends directly on the proper implementation of the norms of the legislation regulating the relations concerning the use and protection of forestry resources, compliance of these norms with the provisions of European legislation and time requirements, as well as on the systematic exercise of state control over the area of use and protection of forestry resources.It has been concluded that it is necessary to improve administrative and legal principles of the use (protection) of the forestry fund objects of the proper legal regulation of relations in this sphere by developing and adopting the Law of Ukraine “On the Forestry Fund of Ukraine”, codification of the forest legislation of Ukraine, systematic review and introduction of relevant amendments to the Forest Code of Ukraine, updating the legal status of the forestry authorities in regard to ensuring the legal regime of the forestry fund.The author considers the scientific development of issues concerning the elaboration of the issues on improving the mechanism of administrative and legal regulation of the legal regime for offenses in the field of use and protection of forestry resources in Ukraine in the context of the implementation of European law into Ukrainian legislation as a perspective direction for further research.